Silage production of corn intercropped with tropical forages in an integrated crop-livestock system with lambs - Pariz, Cristiano Magalhães [UNESP]; Costa, Ciniro [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP]; de Castilhos, André Michel [UNESP]; Andreotti, Marcelo [UNESP]; Costa, Nídia Raquel [UNESP]; Martello, Jorge Martinelli [UNESP] (FapUNIFESP (SciELO), 2017)
The objective of this work was to evaluate the effect of intercropping systems between corn and tropical forages, at different cutting heights, on silage production, light interception, land use efficiency, intercropping competition factors, and pasture production. In the 2010/2011 and 2011/2012 crop seasons, two cultivation modalities were evaluated in the summer/autumn - monocropped corn with residual regrowth of signal grass (Urochloa decumbens) from the soil seed bank and corn intercropped with palisade grass (U. brizantha 'Marandu') -, in a factorial arrangement with two cutting heights for silage production - 0.20 and 0.45 m. After corn silage harvest, the forages were grazed by lambs in a semi-feedlot system, in the winter/spring. Monocropped corn and 0.45-m cutting height both reduced dry matter yield for silage. Corn intercropped with palisade grass improved land use efficiency from 13 to 31% compared with monocropped crop, with land equivalent ratio greater than 1. Palisade grass showed higher light interception than signal grass over the intercrop period with corn and provided greater forage yield for lambs to graze during winter/spring. Corn intercropped with palisade grass, compared with monocropped corn, especially at the cutting height of 0.45 m, is a viable option for improving silage and pasture production, as well as land use efficiency in the integrated crop-livestock system.
Keywords: Cutting height; Land equivalent ratio; Light interception; Urochloa; Zea mays